Alabama Justice : The Cases and Faces That Changed a Nation - Brown, Steven Preston (Book collections on Project MUSE., 2020)
"Unknown to many, Alabama has played a remarkable role in a number of Supreme Court rulings that continue to touch the lives of every American. In Alabama Justice: The Cases and Faces That Changed a Nation, Steven P. Brown has identified eight landmark cases that deal with religion, voting rights, libel, gender discrimination, and other issues, all originating from legal disputes in Alabama. Written in a concise and accessible manner, each case law chapter begins with the circumstances that created the dispute. Brown then provides historical and constitutional background for the issue followed by a review of the path of litigation. Excerpts from the Court's ruling in the case are also presented, along with a brief account of the aftermath and significance of the decision. The First Amendment (New York Times v. Sullivan), racial redistricting (Gomillion v. Lightfoot), the Equal Protection Clause of the Fourteenth Amendment (Frontiero v. Richardson), and prayer in public schools (Wallace v. Jaffree) are among the pivotal issues stamped indelibly by disputes with their origins in Alabama legal, political, and cultural landscapes. In addition to his analysis of cases, Brown discusses the three associate justices sent from Alabama to the Supreme Court-John McKinley, John Archibald Campbell, and Hugo Black-whose cumulative influence on the institution of the Court, constitutional interpretation, and the day-to-day rights and liberties enjoyed by every American is impossible to measure. A closing chapter examines the careers and contributions of these three Alabamians"--